SLC11A1 as a stratification indicator for immunotherapy or chemotherapy in patients with glioma - Xu, Houshi; Zhang, Anke; Fang, Chaoyou; Zhu, Qingwei; Wang, Wei; Liu, Yibo; Zhang, Zeyu; Wang, Xiaoyu; Yuan, Ling; Xu, Yuanzhi; Shao, Anwen; Lou, Meiqing (Frontiers in Immunology, 2022)
Background: Glioma is a fatal tumor originating from the brain, which accounts for most intracranial malignancies. Currently, Immunotherapy has turned into a novel and promising treatment in glioma patients. however, there are still few effective biomarkers to mirror the reaction to immunotherapy in patients with glioma. Therefore, we intended to elucidate the evaluable efficacy of SLC11A1 in glioma patients. Methods: In this study, samples from Shanghai General Hospital and data from TCGA, GEO, CGGA datasets were used to investigate and validate the relationship between SLC11A1 and the progression of glioma. We evaluated the predictive value of SLC11A1 on the prognosis of glioma with cox regression analysis. Then the relationship between immune infiltration and SLC11A1 was also analyzed. Ultimately, we performed the prediction on the immunotherapeutic response and therapeutic drugs according to the expression of SLC11A1. Results: Expression of SLC11A1 increased with progression and predicted unfavorable prognosis for glioma patients. The hazard ratio for SLC11A1 expression was 2.33 with 95% CI (1.92-2.58) (P < 0.001) in cox analysis. And based on expression, we found SLC11A1 stratified glioma patients into subgroups with different immune activation statuses. Moreover, we observed that patients with higher SLC11A1 levels companied with better immunotherapeutic response, while those with lower SLC11A1 levels may respond better to temozolomide. Conclusion: This study provided evidence that SLC11A1 was a novel prognostic marker and immunotherapy response indicator for gliomas. In some cases, SLC11A1 could be an effective marker for identifying patients who might benefit from immunotherapy or chemotherapy.